EFFECT OF PETROLEUM PRODUCT INHALATION ON THE HISTOLOGICAL INDICES OF THE LUNGS OF MALE WISTAR RATS - Offor, Amarachukwu Grace; Edoga, Cyril Onyekachi; Okeke, Chukwuemeka Christian (Advanced Journal of Environmental Sciences (AJES), 2025)
Petroleum product exposure is a known risk factor for respiratory diseases. This study investigated the effect of petroleum product inhalation on oxidative stress parameters and histopathological indices of the lung tissue of male Wistar albino rats. Forty-five rats aged 3 months and weighing 180–220 g were divided into five groups: Group A (Control), Group B (PMS exposure - 500 ml), Group C (Kerosene exposure - 500 ml), Group D (Diesel exposure - 500 ml), and Group E (Mixed petroleum products - 500 ml). The exposure lasted for 28 days, and lung tissue homogenate samples were collected at days 0, 14, and 28 to measure superoxide dismutase (SOD), catalase (CAT) activity and glutathione-s-transferase (GST) activity. The lungs were harvested using dissection to test the histological effects of the exposure. The results showed that SOD and CAT activity were significantly decreased (p<0.05) (11.12 ± 0.48 and 1.63 ± 0.23) when compared with the control (12.87 ± 0.93 and 3.29 ± 0.70) while GST activity significantly increased (p>0.05) (24.02 ± 0.54) compared with the control (23.20 ± 0.45). Histology of the lungs showing degeneration of the dentate granular layer in male Wistar albino rats exposed to diesel. These results emphasize the harmful effects of inhaling petroleum products on critical organ systems, particularly the lungs.